Diversity Analysis of Bacterial and Function Prediction in Hurunge From Mongolia - Bao, Wuyundalai; He, Yuxing; Liu, Wei (Frontiers in Nutrition, 2022)
With the continuous infiltration of industrialization and modern lifestyle into pastoral areas, the types and processing capacity of Hurunge are decreasing, and the beneficial microbial resources contained in it are gradually disappearing. The preservation and processing of Hurunge are very important for herdsmen to successfully produce high-quality koumiss in the second year. Therefore, in this study, 12 precious Hurunge samples collected from Bulgan Province, Ovorkhangay Province, Arkhangay Province, and Tov Province of Mongolia were sequenced based on the V3–V4 region of the 16S rRNA gene, and the bacterial diversity and function were predicted and analyzed. There were significant differences in the species and abundance of bacteria in Hurunge from different regions and different production methods (p < 0.05). Compared with the traditional fermentation methods, the OTU level of Hurunge fermented in the capsule was low, the Acetobacter content was high and the bacterial diversity was low. Firmicutes and Lactobacillus were the dominant phylum and genus of 12 samples, respectively. The sample QHA contained Komagataeibacter with the potential ability to produce bacterial nanocellulose, and the abundance of Lactococcus in the Tov Province (Z) was significantly higher than that in the other three regions. Functional prediction analysis showed that genes related to the metabolism of bacterial growth and reproduction, especially carbohydrate and amino acid metabolism, played a dominant role in microorganisms. In summary, it is of great significance to further explore the bacterial diversity of Hurunge for the future development and research of beneficial microbial resources, promotion, and protection of the traditional ethnic dairy products.